2021
DOI: 10.3390/ijerph18083896
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review to Examine the Evidence in Developing Social Prescribing Interventions That Apply a Co-Productive, Co-Designed Approach to Improve Well-Being Outcomes in a Community Setting

Abstract: This systematic review aims to investigate the evidence in applying a co-design, co-productive approach to develop social prescribing interventions. A growing body of evidence suggests that co-production and co-design are methods that can be applied to engage service users as knowledgeable assets who can contribute to developing sustainable health services. Applying the Preferred Reporting Items for Systemic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic literature search was conducted. Peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 50 publications
2
43
0
2
Order By: Relevance
“…The majority of young people's loneliness scores decreased after engaging with the Linking Leeds service; 50% felt their social networks and relationships had improved and 71% reported a reduction in loneliness. This supports the research conducted by Thomas et al who found the main benefit of social prescribing was the reduction of social isolation, as the young people were able to build a supportive social network [17]. Young people with poor mental health often become isolated, which can have a further negative impact on wellbeing [41].…”
Section: Social Connectednesssupporting
confidence: 81%
See 2 more Smart Citations
“…The majority of young people's loneliness scores decreased after engaging with the Linking Leeds service; 50% felt their social networks and relationships had improved and 71% reported a reduction in loneliness. This supports the research conducted by Thomas et al who found the main benefit of social prescribing was the reduction of social isolation, as the young people were able to build a supportive social network [17]. Young people with poor mental health often become isolated, which can have a further negative impact on wellbeing [41].…”
Section: Social Connectednesssupporting
confidence: 81%
“…The evidence base for social prescribing is growing; however, most studies to date have focused on adults. A recent systematic review found that adults engaging in social prescribing interventions reported an increase in confidence [17]. The authors report this was mainly a result of a reduction in social isolation, as the intervention motivated participants to join social groups and build a social network of support.…”
Section: Social Prescribingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lot of emphasis on stakeholder engagement in policy and practice, but little evidence to demonstrate that a systematic approach to understanding context based on literature review, mapping and stakeholder workshops can lead to novel actions [ 37 , 38 ]. Despite the enthusiastic adoption of concepts such as stakeholder engagement and “co-design”, there is very little evidence to support particular actions that will lead to impacts that could not have otherwise been achieved [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of emphasis on stakeholder engagement in policy and practice, but little evidence to demonstrate that a systematic approach to understanding context based on literature review, mapping and stakeholder workshops can lead to novel actions [37,38]. Despite the enthusiastic adoption of concepts such as stakeholder engagement and "codesign", there is very little evidence to support particular actions that will lead to impacts that could not have otherwise been achieved [39].…”
Section: Discussionmentioning
confidence: 99%